Structural Size Effect with Altered Temperature on MgO-based Magnetic Tunnel Junction Device During Current Flow - Veeraporn Pomsanam; Chanon Warisarn; Apirat Siritaratiwat; Chayada Surawanitkun (My University, 2016)
Recently, the increase in high areal density of hard disk drive with the small bit cells affects the structural variation in the magnetic recording head. Therefore, the structural size effect on the altered temperature in the tunneling magetoresistance (TMR) head with the MgO-based magnetic tunnel junction structure was investigated. Results indicate that the temperature increment in the MgO layer and the antiferromagetic layer decreases significantly with decreasing the thickness of the MgO barrier. This is because the generated heat during the current flow is proportional to the TMR resistance which can be estimated by the resistance of the MgO barrier layer. The efficiency of the write/read process with the thermal effect in the magnetic recording head is the important parameter realized for development of the storage technology.
Keywords: Heat-assisted magnetic recording; Tunnel magnetoresistance; Area density; Magnetic properties of thin films